Cultura corporal Kanhgág nas aulas de Educação Física: uma possibilidade de reafirmar a identidade cultural indígena - KANHGÁG, DIOMARA RÉNHRÁ (2023)
The current study has as its research goal the Phisical Education in the context to the Indigenous School Education. The school education, imposed to the indigenous people during the colonial period, aimed only the assimilation and homogenization of these people to the dominant society. Through many struggles, the indigenous people were able to get with the Federal Constitution from 1988, a more favourable look to the originated people from Brasil. Being assured to the indigenous a specific, differentiated and quality school education, that respect and value the culture, the tradition and the first language of these people. Despite these legislative guarantees, it is noticeable under the indigenous schools the non-compliance of these rights, predominant at this way the curriculum of hegemonic culture. In thise sense, the general goal from the referred study is to register and analyze the body culture of the Kanhgág moviment and its possibilities of incorporation of these practices in Physical Education classes as one of the ways of reaffirmation of cultural identity. The study consists of a qualitative research with approach in field study, that seeks register through interviews, photographic images, observation and field register, the bodily culture of Kanhgág who live on the largest indigenous area from Parana State, the Indignous Area Rio das Cobras located in Nova Laranjeiras municipality. Participated in this research gîr (children), tytãg/kyrû (youths), ag (men), fag (women) and kófa (elderly people) Kanhgág, whereas the interviews were held specifically with our kófa, so they were chosen names of some spirits/guardians to identify our kófa that are they: Vãnh Tãn/Forest Guardian, Ga Tãn/Earth Guardian, Goj Tãn/Water Guardian, Fág Tãn/Araucaria Guardian and Pî Tãn/Fire Guardian. The others contributed in register of photographs and observation. To help me in answering to the research problem, three analysis categories were built through the analysis of photographic registers, interviews and field study, being titled: “Knowing the Kanhgág People and the Indigenous Area Rio das Cobras”, “The Kanhgág Body Practices”, “The Traditional Practices, the Body and the Elder Memories”. As theoric framework I present some authors which address the contextualization of Kanhgág People from Indigenous Area Rio das Cobras by Mota (2009), dualistic social organization, patrilineal, exogamous and matrilocal brought by the authors Tommasino and Fernandes (2001), presence of indigenous in this territory called Parana Antonio Michaele (1969), First Indigenous language Rodrigues (2005), kanhgág dialects by D’Angelis (2002), the traditional indigenous education and the kaingang education found in the speech from the authors Munduruku (2000) and Faustino (2010), the bodly practices from the kanhgág by Fasshember (2006) and other authors, the sports practices in indigenous territory Bracht (2005), the narrated memory brought by Krenak (2020), as many other authors which enrich our dialogue. It is understood, through the analysis, that the knowledge here registered, the newconceptions acquired by the bodly culture from Kanhgág People, from Indigenous Area Rio das Cobras were importante, not only as far as the research and the academic life, but also as change of inner paradigm. So, we believe that there is still much to be done as far as a school indigenous education, which respect the laws that support the right to a specific, differentiated and quality education. Thinking about it, this study presents a vast possibilities of indigenous bodly practices from Kanhgág people that will be able to auxiliary during the Physical Education classes, and this way, contribute to an intercultural education that respect and value the indigenous culture, but mainly put the Kanhgág person as the main protaginist of his/her history, as well as enable the visibility of Kanhgág People present on this territory today called Parana. This study does not end here, neither the knowledge, nor the future possibilities, since there are few studies about this theme from Kanhgág bodly culture of Parana, there are much still needs to be investigated about these people, be by its culture, by it formal or informal education, or other cultural/social elements, that offer many possibilities to the researchers who seek learn the singularity of indigenous representations in different societies from Brazil.